The state-of-the-art review on energy harvesting from flow-induced vibrations - Wang, Junlei; Geng, Linfeng; Ding, Lin; Zhu, Hongjun; Yurchenko, Daniil (Applied energy, 2020)
•The concepts of energy harvesting from flow-induced vibrations are classified.•The methods and principles of flow-induced vibrations energy harvesting are summarized.•The application of energy capture devices and commercially available devices are discussed.•The prospects of the research and application of flow-induced vibrations energy harvesting are presented. In this paper, the currently popular flow-induced vibrations energy harvesting technologies are reviewed, including numerical and experimental endeavors, and some existing or proposed energy capture concepts and devices are discussed. The energy harvesting mechanism and current research progress of four types of flow-induced vibrations, such as vortex-induced vibrations, galloping, flutter and buffeting, are introduced. To enhance the performance of the harvesters and broaden the operating range, the researchers have proposed various mechanical designs, methods of the structures’ surfaces optimization and concepts with incorporated magnets for multistability. The paper summarizes the works led to the current wind energy and hydro energy harvesters based on the principle of flow-induced vibrations, including bladeless generator Vortex Bladeless, University of Michigan vortex-induced vibrations aquatic clean energy, Australian BPS company's airfoil tidal energy capture device bioSTREAM, and others. This shows the gradual progress and maturity of the flow-induced vibrations energy harvesters. The article concludes with a discussion on the current problems in the area of the flow-induced vibration energy capture and the challenges faced.